Molecular dynamics modeling of thorium self-diffusion in the superionic state of ThO2 nanocrystals - Seitov Д.Д.; Nekrasov К.А.; Pitskhelaury С.С.; Boyarchenkov А.С.; Kupryazhkin А.Я.; Gupta С.К. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
Molecular dynamics modeling of the self-diffusion of thorium cations in the volume of isolated ThO2 crystallites with a free surface was carried out. The model systems consisted of 15960 particles, the duration of the computational experiments reached 2 μs. In the superionic state of crystals, a quantitative coincidence of the diffusion coefficients of thorium and oxygen with experimental data extrapolated to high temperatures was obtained. In the temperature range from 2725 K to 3600 K, which included the superionic and crystalline phases, the diffusion of thorium cations in the presence of specially created cation vacancies was studied, and an estimate of the migration energy of cations was obtained equal to (5.9±0.3) eV. The effective activation energies for the diffusion of thorium and oxygen are compared with experimental data.